2017
DOI: 10.1002/ejic.201700648
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of a Stable Phosphonium–Sulfinyl Yldiide

Abstract: The synthesis of a stable lithium phosphonium-sulfinyl yldiide was explored. The compound was fully characterized by NMR spectroscopy and X-ray crystallography. The electronic structure of 2 was analyzed by DFT calculations, which indicated strong ylidic character. Yldiide 2 was stable enough [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…A sulfinyl-stabilized yldiide was reported by Maerten, Baceiredo and coworkers. 39 Lithium yldiide 16 was synthesized by deprotonation with n -BuLi and showed a dimeric structure with a Li 2 O 2 core and decreased P–C and C–S bond lengths owing to the increased negative character at the ylidic carbon center.…”
Section: Alkali Metal Yldiidesmentioning
confidence: 99%
“…A sulfinyl-stabilized yldiide was reported by Maerten, Baceiredo and coworkers. 39 Lithium yldiide 16 was synthesized by deprotonation with n -BuLi and showed a dimeric structure with a Li 2 O 2 core and decreased P–C and C–S bond lengths owing to the increased negative character at the ylidic carbon center.…”
Section: Alkali Metal Yldiidesmentioning
confidence: 99%
“…Apart from Bertrand's α-lithiomethylenephosphorane 79, obtained by formal 1,2-addition of n-butyllithium to an in-situ generated trimethylsilyl-phosphanylcarbene (scheme 93), 196 all of them are obtained following the previous strategy, i.e. deprotonation of an ylide by nbutyllithium 195 or variously metallated amides. 194 In the latter cases, X-ray diffraction studies showed the coordination of the alkali metal by both the carbon and one oxygen from the sulfoxide (in 80) or sulfone (in 81) stabilizing moiety.…”
mentioning
confidence: 99%
“…The C−Au bond lengths [2.056(4) and 2.071(4) Å] are shorter than those observed in the related carbodisphosphorane‐ and carbodicarbene‐diaurated complexes (2.074, 2.078 Å and 2.080, 2.103 Å respectively). The aurophilic interaction is classical with Au1‐Au2 distance of 3.018(1) Å, which is in the range of other gem ‐diaurated carbones (2.952–3.143 Å) . Finally, the P1−C1 [1.781(4) Å] and the S1−C1 [1.737(4) Å] bonds lengths are significantly longer than in 1 , typical for single bonds (P−C: 1.79–1.82 Å and S−C: 1.73–1.75 Å) confirming that the two lone pairs are involved in the formation of complex 4 .…”
Section: Figurementioning
confidence: 97%
“…The phosphine/sulfoxide carbon(0) complex 2 was prepared in two steps from the corresponding chlorophosphonium and methyldiphenylsulfoxonium salts in presence of 2 equivalents of a non‐nucleophilic strong base (LDA) (Scheme ) . In a second step, the deprotonation of salt 1 was performed in THF solution at RT, either with potassium hydride (KH) or potassium hexamethyldisilazane (KHMDS) leading to the selective formation of 2 , which was isolated in 69 % overall yield.…”
Section: Figurementioning
confidence: 99%